MACROECONOMIC INSTABILITY AND BANKS LENDING BEHAVIOUR IN GHANA - Ransford Quarmyne Churchill (European Scientific Journal, ESJ, 2014)
This study aims primarily at investigating the impact ofmacroeconomic instability on banking sector lending behaviour in Ghanausing data on commercial banks and macroeconomic instability from 1992 to2009. My results under the Co-integration and Vector Error CorrectionModeling framework show that bank lending has a long-run relationshipwith macroeconomic instability. The study therefore, recommends that whilebanks should pay adequate attention to the consequences of their firmspecific characteristics in their lending activities both in the short-run andlong-run, their worries about macroeconomic instability should be limited tothe long-run consequences on their lending behaviour. It is also pertinent thatappropriate measures be taken to curtail inflation and sporadic money supplygrowth making banks become unfavourably disposed to lending given theattendant negative consequences of loan curtailment on economic growth inthe long run.